REKONSTRUKSI SISTEM WAKTU DALAM SHUHUF NABI IDRIS - M. Ihtirozun Ni'am; Youla Afifah Azkarrula; Irman Said Prastyo (MIYAH : Jurnal Studi Islam, 2023)
Abstract: Humans in carrying out various activities are very dependent on time. When traced in ancient times, humans marked the time with different references, causing confusion with each other. Therefore, humans are looking for parameters to equalize time. This parameter is the movement of the Sun, Moon and other phenomena. The explanation of the time system is explained in the Book of Enoch. But the explanation is based on that time. So, the question arises of the time system into the present. This research is library research with a qualitative approach. The primary source of this study is the Book of Enoch. The result of this research is it is known that the smallest unit in the book of Enoch is part equivalent to 80 minutes. The day begins with sunrise which occurs for 12 months of the year. One month consists of 30 days with an intercalation of 4 days a year in order to equalize the time of season and solar time so that a year consist of 364 days ending with sabbath. Every month, the sun rises and sets from different places and correlates with constellations. Keywords: Day, The Book of Enoch, Time system.